Seismic Disaster Study Based on Soil Vulnerability Index (Kg) and Peak Ground Acceleration (PGA) Values in Kokap and Surrounding Areas: Studi Kebencanaan Seismik Berdasarkan Nilai Indeks Kerentanan Tanah (Kg) dan Perecepatan Tanah Maksimum (PGA) di Daerah Kokap dan Sekitarnya - Andini, Dita; Nurhaci, Dian Susri (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2024)
Kulon Progo region is one of the areas in Yogyakarta that often experiences natural disasters, especially landslides. With the morphology of mountains that are described as large domes with flat tops and steep wings (Van Bamelen, 1949), making the Kulon Progo area more prone to landslides. Earthquakes with great force can cause landslides in this area. To map areas that are prone to earthquakes and landslides, research using the microseismic method was used. The research is located in Hargorejo Village and Hargowilis Village, Kokap District and Karangsari Village, Pengasih District, DI. Yogyakarta consists of 9 measurement points. Data processing was performed using Geopsy software using the HVSR method. The results showed that the Kokap area and its surroundings had an amplification factor value range of 1-5 times, the natural frequency value was 1.2 Hz to 12.2 Hz, the dominant period value was 0.5-0.8 s, the soil vulnerability index value was , 1 /cm to 2.7 /cm and a PGA value of 64 cm/ to 206.2 cm/ . Based on the research results, the area most vulnerable to the consequences of the earthquake is the village of Hargorejo. The village of Hargorejo which is composed of andesite intrusion has resulted in mineral alteration which produces clay minerals where clay minerals are impermeable so that they easily become sliding fields. When an earthquake occurs, this area will suffer significant damage.